Aplikasi Absensi Guru di SMP Muhammadiyah Tebing Tinggi Kepulauan Meranti Berbasis Android - Abza, Adhamdi Tria Putra; Purjumatin, Purjumatin; Yuliana, Devi (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
Tebing Tinggi Muhammadiyah Middle School is one of the general and religious educational institutions that plays an important role in forming the character Attendance is an important role in every educational institution. Where attendance is one of the main supports that can support and motivate every activity carried out there. Like attendance at Muhammadiyah Tebing Tinggi Middle School which still uses the manual method (signature), this method is very vulnerable for an educational institution because the level of discipline cannot be controlled and can be misused by irresponsible people, other losses that may arise in the manual attendance system, data recapitulation still takes a lot of time and energy, therefore it is felt necessary to use a computer as a tool for processing attendance data using an application designed in such a way that suits the needs of the school concerned.